WHO monographs on selected medicinal plants (World Health Organization, 1999)
A collection of 28 monographs covering the quality control and traditional and clinical uses of selected medicinal plants. Plants were selected for inclusion on the basis of their widespread use, particularly in countries that rely heavily on medicinal plants to meet primary health care needs. Monographs are provided for a number of phytomedicines traditionally used to treat such common complaints as diarrhoea, constipation, headache, appetite loss, sleep disorders, fatigue, and mild respiratory, gastrointestinal, and skin disorders. Additional medical applications assessed range from the lipid-lowering potential of garlic powder preparations, through the possible antiplasmodial activity of Fructus Bruceae, to the role of curcumin in promoting peptic ulcer healing and reducing the associated abdominal pain. In preparing and publishing these monographs, WHO aims to encourage standardized scientific approaches to ensuring the safety, quality and efficacy of medicinal plants and their products. The monographs are also intended to promote international harmonization in the quality control and use of herbal medicines and to serve as models for the development of national formularies. Draft monographs were finalized following review by over 100 experts in 40 countries. Some 1400 references to the literature are included. Each monograph follows a standard format, with information presented in two parts. The first gives pharmacopoeial summaries for quality assurance, botanical features, distribution, identity tests, purity requirements, chemical assays, and active or major chemical constituents. A section on definition provides the Latin binomial pharmacopoeial name, the most important criterion in quality assurance. Latin pharmacopoeial synonyms and vernacular names, listed in the section on synonyms and selected vernacular names, are those names used in commerce or by local consumers. The second part of each monograph begins with a list of dosage forms and of medicinal uses categorized as uses supported by clinical data, uses described in pharmacopoeias and in traditional systems of medicine, and uses described in folk medicine, but not yet supported by experimental or clinical data. Each monograph also includes an extensive review of available data on experimental and clinical pharmacology, followed by information on contraindications, such as sensitivity or allergy, warnings, precautions, particularly in such special groups as pregnant and breast-feeding women, adverse reactions, and dosage. A list of references concludes the monograph. Plants covered in volume 1 Bulbus Allii Cepae Bulbus Allii Sativi Aloe Aloe Vera Gel Radix Astragali Fructus Bruceae Radix Bupleuri Herba Centellae Flos Chamomillae Cortex Cinnamomi Rhizoma Coptidis Rhizoma Curcumae Longae Radix Echinaceae Herba Echinaceae Purpureae Herba Ephedrae Folium Ginkgo Radix Ginseng Radix Glycyrrhizae Radix Paeoniae Semen Plantaginis Radix Platycodi Radix Rauwolfiae Rhizoma Rhei Folium Sennae Fructus Sennae Herba Thymi Radix Valerianae Rhizoma Zingiberis
Keywords: medicína; Léčivé rostliny; Rostliny léčivé